The nature of the early Ottoman state - Lowry, Heath W., 1942- (State University of New York Press, 2003)
Drawing on surviving documents from the fourteenth and fifteenth centuries, The Nature of the Early Ottoman State provides a revisionist approach to the study of the formative years of the Ottoman Empire. Challenging the predominant view that a desire to spread Islam accounted for Ottoman success during the fourteenth-century advance into Southeastern Europe, Lowry argues that the primary motivation was a desire for booty and slaves. The early Ottomans were a plundering confederacy, open to anyone (Muslim or Christian) who could meaningfully contribute to this goal. It was this lack of a strict religious orthodoxy, and a willingness to preserve local customs and practices, that allowed the Ottomans to gain and maintain support. Later accounts were written to buttress what had become the self-image of the dynasty following its incorporation of the heartland of the Islamic world in the sixteenth century.
Keywords: Turkey -- Civilization.; Turkey -- Social conditions.; Turkey -- History.; Turquie -- Conditions sociales.; Turquie -- Histoire.; HISTORY -- General.; Civilization; Social conditions; Turkey; History